A study on scantling formulae of plate members due to lateral pressure under the effect of axial loads. (November 2021) - Umezawa, Rikuto; Naruse, Yoshiaki; Okada, Tetsuo; Kawamura, Yasumi; Ishibashi, Kinya; Koyama, Hiroyuki
Abstract: Existing rule scantling formulae of plate members are based on conventional plastic design theory, and do not necessarily reflect complicated plate bending phenomena under axial loads. In this study, we first formulated the effect of axial load on the fully plastic moment based on the von Mises yield criterion for longitudinally stiffened plate in addition to the well-known formula for transversely stiffened plate. In addition, we derived a theoretical formulation of the lateral pressure corresponding to 2-point hinge and 3-point hinge formation taking account of the effect of the additional lateral force due to the axial loads on the deflected plating, using a simple plate strip bending model assuming a long plate with a large aspect ratio. Then, a series of elastic-plastic FE analyses was carried out to verify the structural behavior and the effect of axial load on the plate plastic bending strength. The plate strength was evaluated based on the residual deflection criteria of two cases (0.26 mm and 4.0 mm), and the results were compared with the theoretical derivation. As a result, it was found that assumption of linear strength reduction to the axial stress can cover the transversely stiffened plate under compressive axial stress conservatively. As to the transversely stiffened plate under tensile axial stress and the longitudinally stiffened plate, the strength reduction was in accordance with the reduction in the fully plastic moment based on the von Mises yield criterion in the conservative side. Finally, based on the findings, the required plate thickness coefficients were proposed on an empirical basis both for transversely and longitudinally stiffened plate under compressive and tensile axial loads. Highlights: Theoretical formulation of hinge formation of a plate under lateral pressure and axial load. Comparison between the results of the derived formulae and of elastoplastic FEA based on residual deflection criteria. Proposal of new required plate thickness coefficients due to the effect of axial load, based on the observations. Especially new formula for the longitudinally stiffened plating.